KINERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN DONGGALA - Yolanda Widyasari; Daswati Daswati; Sitti Chaeriah Ahsan (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Yolanda Widyasari, Stambuk Number B102 22 086, with the research title Employee Performance of the Regional Secretariat of Donggala Regency, supervised by Daswati, and Sitti Chaeriah Ahsan This study aims to determine Employee Performance at the Regional Secretariat of Donggala Regency. This research uses methods with descriptive qualitative data. The research location is at the Regional Secretariat of Donggala Regency. The theory used in this research is the theory put forward by Robbins, Stephen P. Informants in this study amounted to 5 (five) people. The data obtained in this study are from the results of observations, interviews, and documentation. The data analysis method is Data Collection, Data Condensation, Data Presentation, and Conclusion Drawing / Verification.The results of this study indicate that Employee Performance at the Regional Secretariat of Donggala Regency has not been running optimally, this is due to the non-achievement of the performance indicators used in this study, such as the quality aspect which has been maximized due to the implementation of tasks based on the applicable SOP. The aspect of quantity that has not been maximized because it has not been maximized because there are still a number of activities that do not reach the target. The timeliness aspect has not been running optimally due to frequent delays in completing tasks. Aspects of effectiveness with adequate resource support do not necessarily encourage the achievement of targets, so that the effectiveness is not maximized.